Cathedrals as Instruments of Influence on Public Consciousness in Medieval Western Europe (10th-16th Centuries) - V. V. Bondareva (Научный диалог)
This study explores the functional impact of Christian cathedrals in Western Europe on medieval public consciousness. Utilizing a systemic analysis method and a values-based approach, cathedrals are examined as structural elements within the framework of religious communication, serving as key instruments for shaping public consciousness during the Middle Ages. Through these edifices, the core tenets of Christianity were disseminated to the masses. Special attention is given to the art of stone calendars, which are considered a significant factor in the formation of a Christian worldview during this period. The study identifies the value-laden, symbolic, and functional characteristics of medieval cathedrals as tools of religious communication. It outlines the overarching principles of architectural organization in Catholic churches in relation to their roles in influencing public consciousness. The influence of Romanesque cathedrals on the trajectory of public consciousness in medieval Western Europe is also examined. The author concludes that Christian cathedrals, as instruments of influence on medieval public conscious-ness, possessed a pronounced managerial and motivational effect, fulfilling a wide range of sociocultural functions that contributed to the stabilization and spiritual-moral development of medieval Western European society.